Air temperature rises in compressor and turbine stator wells - Bayley,FJ; Childs,PRN (1994)
This paper considers the fluid dynamic principles determining the consequences of mainstream fluid ingressing to the comparatively shallow space between the rotor disc and the ring used in many designs of axial-flow turbo-machine, especially compressors, to support the stator blades at their inner ends. Windage power due to friction between this fluid and the bounding walls of this annular space, or 'stator well', can lead to substantial temperature rises in this region. The feasible range of flow regimes is first developed, especially as influenced by leakage through the internal seals beneath the stators separating adjacent wells. Using published data, on windage coefficients and the effects of geometry on the flow through the wells, very little of which has been obtained from truly representative flow conditions or geometries, calculations have been made to estimate the likely rises in temperature to be anticipated in realistic well designs. Leakage rates appear, not unexpectedly, to be crucial in determining these temperature rises, but the geometries of the system are little less critical, in particular the ratio of the outer to inner radiuses of the stator well and the outer peripheral clearances between rotor and stator surfaces. Leakage into a well from its adjacent neighbour is shown to lead to higher temperature rises downstream of the labyrinth seal and the possible effects of recirculation through stator wells from the mainstream boundary layer could be significant.